Integration of Extracorporeal Membrane Oxygenation into the Management of High-Risk Pulmonary Embolism: An Overview of Current Evidence - Chopard, Romain; Morillo, Raquel; Meneveau, Nicolas; Jiménez, David (Hämostaseologie, 2024)
High-risk pulmonary embolism (PE) refers to a large embolic burden causing right ventricular failure and hemodynamic instability. It accounts for approximately 5% of all cases of PE but contributes significantly to overall PE mortality. Systemic thrombolysis is the first-line revascularization therapy in high-risk PE. Surgical embolectomy or catheter-directed therapy is recommended in patients with an absolute contraindication to systemic thrombolysis. Extracorporeal membrane oxygenation (ECMO) provides respiratory and hemodynamic support for the most critically ill PE patients with refractory cardiogenic shock or cardiac arrest. The complex management of these individuals requires urgent yet coordinated multidisciplinary care. In light of existing evidence regarding the utility of ECMO in the management of high-risk PE patients, a number of possible indications for ECMO utilization have been suggested in the literature. Specifically, in patients with refractory cardiac arrest, resuscitated cardiac arrest, or refractory shock, including in cases of failed thrombolysis, venoarterial ECMO (VA-ECMO) should be considered, either as a bridge to percutaneous or surgical embolectomy or as a bridge to recovery after surgical embolectomy. We review here the current evidence on the use of ECMO as part of the management strategy for the highest-risk presentations of PE and summarize the latest data in this indication.
Keywords: pulmonary embolism; extracorporeal membrane oxygenation; pulmonary revascularization; multidisciplinary care